Interpretasi Ekonomi dalam Resepsi Pembaca pada Akun @Fiksimini di Twitter - Arini Vika Sari (Graha Mitra Edukasi, 2022)
Twitter has become one of the forums used to introduce mini fiction literary works. One of the accounts that tries to bind Twitter users to be interested, like and participate in creating fictionmini literary works is the @fiksimini account. With different forms and characteristics, the @fiksimini account can make its followers and readers respond to topics that are thrown and cause economic interpretations. This study aims to analyze forms of economic interpretation that come from the reception of readers of the @fiksimini account on Twitter. This research uses descriptive qualitative research. The data source used was the @fiksimini account on Twitter during July 2019 to July 2020. Data collection was carried out using reading and note-taking techniques. The data collection instrument is the researcher himself (human instrument) using Iser's literary reception parameters. The data analysis technique in this study uses semantic and pragmatic equivalents in analyzing reader comments based on their economic interpretations. The data analysis stage was carried out in three stages, namely (1) word reduction; (2) data presentation; and (3) drawing conclusions. The results show that there are six forms of economic interpretation, namely the form of difficulty in getting a job by 30.1%, the form of being a guarantor by 11%, the form of caste differences by 11%, the form of running out of inventory by 7%, and the form of shares amounting to 3.1 %. The forms of economic interpretation contained in the @fiksimini account can provide an illustration that most Indonesian people are still far from a prosperous and prosperous life